SURFACE ROUGHNESS OF BULK-FILL RESIN-BASED COMPOSITE RESTORATIVE MATERIALS AFTER IMMERSION IN PROBIOTIC MILK - Florence Brenda Fadewi; Isyana Erlita; Debby Saputera (FKG Unlam, 2019)
Background: Dentists often restore posterior cavities caused by caries using the latest resin-based composite; i.e. bulk-fill resin-based composite. Probiotic milk may affect the surface roughness because the acid content may induce degradation of filler components resulted in roughness on the surface of bulk-fill resin-based composite. Objective: This study aims to determine the surface roughness of bulk-fill resin-based composite restorative materials after immersion in probiotic milk for 10 hours and 20 hours. Method: The study applied true experimental method using pretest and posttest with control group design. The research sample was obtained using simple random sampling. This study employed 8 samples which were included in 4 treatments. Thus, the total number of samples used was 32 samples. Results: The average value of surface roughness in group I was 0.2675 µm, group II was 0.4138 µm, group III was 0.0900 µm and group IV was 0.0938 µm. The results of One-Way ANOVA parametric test revealed p value = 0.000 (p < 0.05) and presented that the immersion of bulk-fill resin-based composite in probiotic milk for 20 hours obtained the highest average surface roughness value compared to the immersion in distilled water and probiotic milk for 10 hours. Conclusion: There is an increase in surface roughness of bulk-fill resin-based composite restorative material after immersion in probiotic milk for 10 hours and 20 hours.